Cartilage Oligomeric Matrix Protein Levels in Synovial Fluid in Patients With Primary Knee Osteoarthritis And Healthy Controls: A Preliminary Comparative Analysis With Serum Cartilage Oligomeric Matrix Protein - Ruben Daniel ARELLANO,; Lizette Sarai AGUILAR,; Rafael ARGÜELLO,; Fernando HERNADEZ,; Faviel Francisco GONZALEZ,; Javier MORAN, (Archives of Rheumatology, 2017)
Objectives: This study aims (i) to compare synovial fluid and serum cartilage oligomeric matrix protein levels in patients with primary knee osteoarthritis and healthy controls, (ii) compare variations of synovial fluid and serum cartilage oligomeric matrix protein levels according to sex, Kellgren-Lawrence grades, and daytime sampling, and (iii) correlate the synovial fluid and serum cartilage oligomeric matrix protein levels with age, severity of disease, and daytime sampling. Patients and methods: One hundred and twenty-four individuals (44 males, 80 females; median age 66 years; range 42 to 87 years) were diagnosed with primary knee osteoarthritis according to the American College of Rheumatology guidelines. Additionally, 105 healthy healthy individuals (49 males, 56 females; median age 50 years; range 30 to 75 years) were included as the control group. For both groups, a thorough clinical history and physical examination were performed. Moreover, weight-bearing anteroposterior and lateral bending 30 degrees knee X-rays were collected. Cartilage oligomeric matrix protein in serum and synovial fluid was measured by enzyme-linked immunosorbent assay. Results: Total synovial fluid cartilage oligomeric matrix protein levels were considerably higher than total serum levels for both groups. Levels of cartilage oligomeric matrix protein in synovial fluid and serum were higher in patients than in controls for both sexes. However, only cartilage oligomeric matrix protein levels in synovial fluid were higher in female patients. The levels of synovial fluid cartilage oligomeric matrix protein were significantly higher when sampling after 12 pm. A positive correlation was found between synovial fluid and serum cartilage oligomeric matrix protein levels, age, and daytime sampling. Conclusion: These findings may suggest a possible role for synovial fluid and serum cartilage oligomeric matrix protein as a measure for primary knee osteoarthritis. However, more studies need to be performed to address other factors that may influence the levels of cartilage oligomeric matrix protein in synovial fluid and serum.